Bioethanol production from azolla filiculoides using saccharomyces cerevisiae - Christy, E.J.S.B.A.; Kapilan, R.; Wickramasinghe, I.; Wijesekara, W.L.I. (university of Jaffna, 2020)
Ethanol can be produced from any material that contains sugar, starches and cellulosic materials are used as an ideal and inexpensive raw material in the production of ethanol by fermentation. Cellulosic substrates are easily hydrolyzed into sugars by way of the action of enzymes. Huge amount of diverse under-utilized aquatic sources which are rich in cellulosic substrates are excessively available and widely distributed in Sri Lanka especially in Northern Province. This study was aimed to screen the potential aquatic plants as substrate for ethanol production and to optimize the conditions to obtain higher yield. Fresh water vegetation species such as Azolla filiculoides, Nelumbo nucifera, Lemna minor, Wolffia globosa, Wolffia arrhiza, Lemna minor and Cabomba caroliniana were used as substrates for ethanol production by using baker's yeast; Saccharomyces cerevisiae, with the liquid fermentation system. Significantly higher amount (0.2%) of bioethanol was produced using Azolla filiculoides as substrate. Azolla filiculoides was selected for further studies and pretreated with 50 ml of 3% (w/v) acid solutions (H2SO4, HNO3 and HCl) and 3% (v/v) alkaline solutions (NaOH and KOH). Significantly higher amount of yield (0.2%) was obtained with H2SO4. Therefore, H2SO4 was selected as the best hydrolyzing agent and different concentrations (1-10%) were used for pretreatment.Significantly higher amount of ethanol (0.4%) was measured at 6% of H2SO4. When the substrates were hydrolyzed with different incubation periods (15min, 30min and 45min), significantly higher amount of alcohol (0.4%) was obtained at 15 min of incubation period. All the containers were incubated and alcohol was measured at every 12 hours, higher amount of yield (0.5%) was obtained at 54 hours of fermentation time. when fermentation was carried out with baker's yeast inoculated with peptone, yeast extract and nutrient (PYN) medium at room temperature and pH 7.0 and under the optimized conditions such as 6% of (50ml) H2SO4 pretreatment, 15 minutes of incubation period and 54 hours of fermentation time, the ethanol production with Azolla filiculoides by Saccharomyces cerevisiae was increased by 2.5 times than the non- optimized conditions.
Keywords: Azolla filiculoides; Bioethanol; Fermentation; Pretreatment; Hydrolysis; Saccharomyces cerevisiae